Power spectrum analysis of fetal heart rate variability at near term and post term gestation during active sleep and quiet sleep - van Laar, J.O.E.H.; Peters, C.H.L.; Vullings, R.; Houterman, S.; Oei, S.G. (Early human development, 2009)
Spectral analysis of fetal heart rate variability is promising for assessing fetal condition. Before using spectral analysis for fetal monitoring it has to be determined whether there should be a correction for gestational age or behavioural state. Compare spectral values of heart rate variability between near term and post term fetuses during active and quiet sleep. Case–control. Cases had a gestational age of ≥ 42 weeks; controls were 36 to 37 weeks. Fetuses were matched for birth weight percentile. STAN ® registrations from healthy fetuses. For each fetus one 5-minute segment was selected during active and one during quiet sleep. Absolute and normalized low (0.04–0.15 Hz) and high frequency power (0.4–1.5 Hz) of heart rate variability. Twenty fetuses were included. No significant differences were found between cases and controls in absolute (481 and 429 respectively, P = 0.88) or normalized low (0.78 and 0.80 respectively, P = 0.50) or absolute (41 and 21 respectively, P = 0.23) or normalized high frequency power (0.08 and 0.07 respectively, P = 0.20) during active state. During rest, normalized low frequency power was lower (0.58 and 0.69 respectively, P = 0.03) and absolute (16 and 10 respectively, P = 0.04) and normalized high frequency power were higher (0.21 and 0.14 respectively, P = 0.01) in cases compared to controls. Absolute and normalized low frequency power were higher during active state compared to rest in both groups (all P values < 0.05). We found sympathetic predominance during active state in fetuses around term. Post term parasympathetic modulation during rest was increased compared to near term.